Design of a Multi-Tenant Database for a Village Water Management Information System (Nusa Tirta) - aulia; Dinar Mustofa; Rizki Cahya Putri; Intan Nur Sifa; Mayza Nurul Khasanatun Nisa; Purnia Setiawati; Sri Rahayu; Lina Nur Afifah (Universitas Lampung, 2026)
Village water management through BUMDes often faces challenges due to inefficiency resulting from the use of a recording system that is still manual, prone to errors and lacks transparency. This study aims to design a structured database for the